Demokrasi dan Kontradiksi-Kontradiksinya, Perspektif Sejarah Filosofis Pierre Rosanvallon - Dua, Mikhael (Institut Filsafat dan Teknologi Kreatif Ledalero, 2024)
This Article discusses on Pierre Rosanvallon’s conceptual history of democracy both as a method to understand the antinomy and the pathology of democracy and as a reflection of the generality of moral politics. Using a philosophical analysis, it answers the philosophical problem of man’s desire to be recognized as a human being with dignity in democracy into three parts: the first one deals with Rosanvallon’s conceptual history of democracy, the second part delves into the problem of antinomy and pathology of democracy, and the third part focuses of the search for the empirical normativity which is based on the moral generality. The article arrives at the idea that behind the political contradictions in democracy Rosanvallon puts the empirical normativity which is based on social relationship into his conceptual history of democracy as a condition of possibility of political recognition. Keywords: Conceptual History, Democracy, Empirical Normativity, Epikeia, Pathologies, Piere Rosanvallon.